2006
DOI: 10.1210/en.2005-1378
|View full text |Cite
|
Sign up to set email alerts
|

Estrogen Modulates the SpinalN-Methyl-d-Aspartic Acid-Mediated Pelvic Nerve-to-Urethra Reflex Plasticity in Rats

Abstract: The effects of gonadal steroids on glutamate-mediated pelvic nerve-to-urethra reflex (PUR) plasticity were investigated in rats, which received a sham operation (Sham), ovariectomy (OVX), or ovariectomy with daily supplemental estrogen (50 microg/kg, OVX + E2). The magnitude of the repetitive stimulation (RS, 1 Hz)-induced potentiation in PUR activity decreased significantly in the OVX group when compared with the Sham groups (18.09 +/- 3.91 and 7.40 +/- 1.03 spikes/stimulation in Sham and OVX group; respectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
25
0

Year Published

2007
2007
2013
2013

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 36 publications
0
25
0
Order By: Relevance
“…Recently, the nerve-mediated reflex urethral closure mechanisms have been considered to contribute to the urethral resistance during events causing elevation of intravesical pressure (P ves ) in rats (14). Electrophysiological studies also have provided evidence indicating functions of the glutamate-mediated bladder-to-urethra reflexes in rats (6,16,17). With the accumulation of findings of active urethral closure mechanisms, pharmacotherapy by drugs that augment the reflex urethral closing mechanisms is accepted (4,10,23).…”
mentioning
confidence: 99%
“…Recently, the nerve-mediated reflex urethral closure mechanisms have been considered to contribute to the urethral resistance during events causing elevation of intravesical pressure (P ves ) in rats (14). Electrophysiological studies also have provided evidence indicating functions of the glutamate-mediated bladder-to-urethra reflexes in rats (6,16,17). With the accumulation of findings of active urethral closure mechanisms, pharmacotherapy by drugs that augment the reflex urethral closing mechanisms is accepted (4,10,23).…”
mentioning
confidence: 99%
“…These impulses, therefore, induce EUS contraction to establish sufficient intravesical pressure for urine propulsion (11,29). Recent studies investigating SRP in pelvic nerve-to-EUS reflex activity have demonstrated that not only the pelvic nerve-to-EUS reflex activity itself but also the stimulationinduced SRP in such a reflex may play an important role in the urethra closure mechanism (31)(32)(33)(34)(35)(36). In the present study, superimposed pontine tegmentum stimulation produced facilitation in RS-induced SRP in pelvic nerve-to-EUS reflex activity, which suggests that descending modulation coming from the pontine tegmentum may also be essential for the physiological urethra closure functions.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, using in vivo animal preparations, we demonstrated that low-frequency repetitive stimulations (RS) on the pelvic afferent nerve might elicit a novel form of activitydependent reflex plasticity, i.e., a spinal reflex potentiation (SRP) in pelvic nerve-to-EUS reflex activity (9,10,(31)(32)(33)(34)(35)(36). Such an animal model is quite different from investigations using brain or spinal slices with a thickness of several millimeters and may maintain the whole neural network within the central nervous system as well as all the dorsal and ventral rootlets attached on the spinal cord intact, thereby offering a gateway to investigate modulations on the SRP resulting from a specific neuronal projection to the site where SRP occurs.…”
mentioning
confidence: 99%
“…Recent studies on pelvic-urethra reflex, using intact spinal cord preparations, have demonstrated a glutamatergic N-methyl-D-aspartate (NMDA)-dependent spinal reflex potentiation in which the activity of this reflex was dynamically potentiated by repetitive (29) and tetanic (30) afferent inputs. Because pathological potentiation in this reflex activity was suggested to underlie the hyperactive urethra (10, 11, 26 -28), the activity-dependent spinal reflex potentiation seems to be a novel animal model for studying urethra continent function (12,13,28,39,(41)(42)(43)(44).…”
mentioning
confidence: 99%